The cocktail diaries : a spirited adventure - Heughan, Sam, 1980- (Quadrille, 2025)
"Sam Heughan's acting career has led him on a unique journey around the world and his love of craft spirits, history, and travel is distilled into this personal collection of cocktail recipes. The Cocktail Diaries includes chapters on Sam's Top 10 all-time favorites, "Simple and Timeless" recipes for those easy crowd-pleasers, "Complex and Conversational" for something a bit more sophisticated, and a final section, "Made by Friends", featuring imaginative recipes created by international bartenders for Sam and his brand Sassenach Spirits--a tailormade tour of the world's best cocktails. Sam's expertise and enthusiasm shine through, as he regales tales of tasting cocktails--from the historic Boulevardier in Paris and a Bramble in New Orleans to a Papaya Margarita in the back of a van in the Oaxaca mountains--and delights in sharing his favorite adventures (and drinks!) with the reader."--